2021
DOI: 10.3389/fpsyg.2021.609842
|View full text |Cite
|
Sign up to set email alerts
|

“Who Champions or Mentors Others”? The Role of Personal Resources in the Perceived Organizational Politics and Job Attitudes Relationship

Abstract: Drawing insight from affective events theory, this study presents a new dimension of perceived organizational politics and job attitudes. The motivation for this study was based on the fact that perceived organizational politics affect job attitudes and that personal resources (political skill and work ethic) moderate the direct relationship between perceived organizational politics and job attitudes in the context of the higher-education sector. In this regard, the data was collected through purposive samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 132 publications
(212 reference statements)
0
18
0
Order By: Relevance
“…Finally, scholars explained that instituting HPWPs culture in organizations enables the workforce to develop skills aligned with the organizational goals and strategies (MacDuffie, 1995). Empirical studies have suggested that implementing HPWPs in the organizational arena (Kim and Liu, 2017;Iqbal, 2019;Kumar and Reddy, 2019;Nansubuga et al, 2019;Ogbonnaya and Messersmith, 2019) leads to different positive consequences such as increased well-being, knowledge sharing behavior (Ali et al, 2021), and high individual and organizational performance (Khan et al, 2021). Furthermore, HPWPs enable employees to gain resources that increase EIRP and ETP through ability, motivation, and participation at the workplace.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Finally, scholars explained that instituting HPWPs culture in organizations enables the workforce to develop skills aligned with the organizational goals and strategies (MacDuffie, 1995). Empirical studies have suggested that implementing HPWPs in the organizational arena (Kim and Liu, 2017;Iqbal, 2019;Kumar and Reddy, 2019;Nansubuga et al, 2019;Ogbonnaya and Messersmith, 2019) leads to different positive consequences such as increased well-being, knowledge sharing behavior (Ali et al, 2021), and high individual and organizational performance (Khan et al, 2021). Furthermore, HPWPs enable employees to gain resources that increase EIRP and ETP through ability, motivation, and participation at the workplace.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…This argument is supported by empirical findings repeatedly highlighting POP negatively affecting employees' well-being as well as organizational outcomes. POP has been found associated with a diverse attitudinal and behavioral outcome for example, job satisfaction (Khan et al,2018;khan et al,2019), organizational citizenship behavior, in-role performance (Byrne, 2005), burnout and low performance at work (Harris, Andrews, & Kacmar, 2007), job related negative emotions and outcomes (Khan et al,2021) producing job tension as well as emotional exhaustion (Hall et al, 2017). Of many attitudinal and behavioral outcomes of POP, intention to quit seems very important, as intention to leave is a strong predictor of actual turnover (Harris, Andrews, & Kacmar, 2007).…”
Section: Perceived Organizational Politics (Pop)mentioning
confidence: 99%
“…This last factor namely pay and promotion policies is related to the way organizations behave politically while implementing the policies (Kacmar & Ferris, 1991 as cited in Kacmar & Carlson, 1997, p, 629;Kacmar & Ferris, 1993;Kacmar & Carlson, 1997, p, 631). Such practices in the organizations, e.g., inequitable reward, unfairness and discrimination in the organization lead employees to behave in a negative way, show anger and distress and intentions to quit job (Adebayo, Sunmola, &Udegbe, 2008).Employees who perceive discrimination in rewards from the organization more likely engage in political behaviors themselves (Kacmar &Carlson, 1997, p, 631).These predictors of intentions to quit have been researched widely in past literature including hostile attribution style of individuals at workplace (Harvey, Harris, & Martinko, 2008), unfairness and discrimination in rewards and promotion policies (Oluwafemi, 2013) and POP in their environment (Khan et al, 2021).Therefore, we hypothesized that:…”
Section: Pop and Intentions To Quitmentioning
confidence: 99%
See 1 more Smart Citation
“…Public sector organizations are challenged with poor performance of employees in developing countries (Chughtai & Shah, 2020). Employees in public sector organizations feel less satisfied than the corporate sector, which also becomes the cause of low performance (Khan et al, 2021). It has been observed in the earlier studies that job satisfaction (JS) has become an interesting research topic, especially in the context of public sector organizations (DeHart-Davis, Davis, & Mohr, 2015;Overman, 2020).…”
Section: Introductionmentioning
confidence: 99%